Between Exits : Paintings by Hani Zurob - Boullata, Kamal; Fisher, Jean; Zurob, Hani (London; Black Dog Publishing, 2012)
Between Exits is the fist monograph to trace the evolution of Palestinian artist Hani Zurob, from his initial paintings produced in Palestine, through to his most recent works, developed during the artist$1 (Bs exile in France. The volume is organized chronologically to offer the reader a comprehensive insight into Zurob$1 (Bs key paintings and series of the past two decades. Writer and curator Kamal Boullata takes the reader through Zurob$1 (Bs artistic development and carefully reveals how each body of work reflects the evolving approaches to the understanding of self as well as strategies of collective belonging, which the artist$1 (Bs work constantly addresses. The conflicted Palestinian identity is recurrently mediated and questioned throughout Zurob$1 (Bs work. Between Exits simultaneously evokes the notion of movement and displacement that are central to the Palestinian everyday reality.s
English
Keywords: ND49-813 Painting- History; Palestine